Faktor Yang Mempengaruhi Pemberian Imunisasi Dasar Lengkap pada Bayi di Puskesmas Srikaton Tahun 2023 - Sari, Febri Indah; Ciselia, Dewi; Afrika, Eka (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
The World Health Organization (WHO) states that immunization in 2021 prevents 3.5-5 million deaths each year from diseases such as diphtheria, tetanus, pertussis, influenza and measles. Factors that influence the provision of complete basic immunization to infants include knowledge, education, and family support. The purpose of this study was to determine the factors influencing the provision of complete basic immunization to infants at the Srikaton Health Center in 2023. The research design used analytic observational, with a cross-sectional design. The population in this study were mothers who had babies aged 12-18 months. The sampling technique in this study was carried out by means of purposive sampling with a total sample of 62 respondents, collecting data using a questionnaire. Data analysis used univariate analysis and bivariate analysis using the chi square test. The results of the study show that there is a relationship between knowledge (p value 0.01), education (p value 0.02), and family support (p value 0.01) with the completeness of immunization at the Srikaton Health Center in 2023. It is hoped that the results of this study can be an illustration for the puskesmas to further improve the provision of complete basic immunization by providing information to mothers who come for immunization about the schedule and benefits of immunization